A prolonged activated partial thromboplastin time indicates poor short-term prognosis in patients with hepatic encephalopathy: insights from the MIMIC database - Zhan, Liping; Yang, Yuping; Nie, Biao; Kou, Yanqi; Du, Shenshen; Tian, Yuan; Huang, Yujie; Ye, Ruyin; Huang, Zhe; Luo, Botao; Ge, Lei; Ye, Shicai (Frontiers in Medicine, 2025)
ObjectivesThis study investigates serum markers for short-term prognosis in hepatic encephalopathy patients.BackgroundPatients with hepatic encephalopathy face elevated mortality rates and bleak prognoses. However, effective prognostic models or indicators are lacking. This study aims to explore serum markers for predicting short-term prognosis in these patients.MethodsWe conducted a retrospective analysis of 552 patients with hepatic encephalopathy, categorizing 429 individuals meeting exclusion criteria into normal and high activated partial thromboplastin time (APTT) groups. We assessed 12-day and 25-day survival rates using Kaplan–Meier analysis and Cox regression models to examine associations between groups and outcomes.ResultsUpon comparing baseline characteristics, the high APTT group exhibited significant disparities in acute kidney injury, sepsis, coagulation disorders, and ascites (p < 0.05). In the multivariate COX regression model, the hazard ratios [HRs; 95% confidence interval (CI)] of 12- and 25-day mortality were 1.012 (1.001, 1.022, p = 0.033) and 1.010 (1.002, 1.018, p = 0.013), respectively. We discovered that APTT demonstrated an independent association with prognosis. Our findings revealed that the ability of APTT to predict short-term prognosis surpasses that of the traditional MELD model. Regarding 12- and 25-day survival, Kaplan–Meier survival curves from these groups demonstrated a lower survival probability for patients in the high APTT group than the normal group (log-rank p < 0.05). The results of subgroup analysis and interaction analysis indicate that APTT is not influenced by other confounding factors.ConclusionA prolonged APTT suggests a poorer short-term prognosis in patients with hepatic encephalopathy.